Organizational Commitment and Job Performance of Cataloguers in Libraries in Ogun State, Nigeria - Bamidele, Itunu Adeola; Akalawu, Goodness Tochi; Adesina, Odunola Ibiyemi (Communicate: Journal of Library and Information Science, 2025)
The study investigated the Organizational commitment and job performance of cataloguers in Libraries in Ogun State, Nigeria. The descriptive survey design was adopted for the study. The study employed total enumeration technique to capture 210 libraries in Ogun State Nigeria with minimum qualification of first degree in Library and Information Science (LIS). A questionnaire tagged Organizational commitment and Cataloguers’ job performance in libraries in Ogun state, Nigeria was used as instrument for data collection Data were analysed using percentages, mean, standard deviation and Pearson product moment correlation. The findings of this study revealed that level of cataloguers’ job performance (mean=2.92) and organizational commitment (mean=2.66) were on an average level. The study found significant correlation between organizational commitment and job performance of cataloguers. Based on the findings the study concluded that committed cataloguers in libraries in Ogun State, Nigeria can facilitate easy execution of library activities thereby fostering the attainment of library goals. Therefore, library management should motivate the library staff by ensuring that they are well remunerate to improve on the commitment of the cataloguers.